Human Rights and Digital Censorship as Legal Boundaries to Control Access to Pornographic Content - Taufik, Moh; Aranggraeni, Renda; Fitria, Yati; Wijaya , Alex Sandi (Intitute of Computer Science (IOCS), 2024)
This research aims to analyze the legal considerations that prevent a person from being convicted when accessing pornographic content and identify the implications that arise from the consumption of such content. The main focus of this research is how legal regulations in various countries, including Indonesia, regulate access to pornography and the extent of the application of criminal law. The research method used is a normative juridical method with a statute approach and conceptual approach. Data is obtained through literature study, including rules and regulations, court decisions, academic literature, and social media. The results show that the non-criminalization of individuals who access pornography is based on the principle of no crime without a clear legal basis and the right to individual privacy. Most regulations place more emphasis on criminalizing the production, distribution, and dissemination of pornographic content than personal consumption. However, some countries apply exceptions in some instances, such as the consumption of child pornography, which is expressly prohibited.